ANALYSIS OF RECENT SURFACE DEVELOPMENT ON THE HIGH BLUFF BETWEEN PAKS AND DUNAKÖMLŐD - Magyar, A.; Fábián, Sz. Á.; Kovács, I. P.; Varga, G.; Radvánszky, B.; Kovács, M.; Sobucki, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The constantly recurring mass movements are highlighted geohazards of Hungary. Surface movements of these types have been posing risk and danger to several high bluff stretches on the right bank of the Danube over the past 50 years. One of the most affected areas is located around Dunakömlőd. The Danube has been eroding laterally the loess, and loess-type formations of the high bluffs for at least 10 thousand years. Former engineering geological studies primarily analyzed the bluffs around and in the town of Paks. Recently new movements have been identified in Dunakömlőd where detailed geomorphological studies have not yet been carried out hitherto. Analyses and exploration of surface movements are particularly important for regional development plans, local government projects and especially for the safety of local residents. The embankment regression rate was estimated based on the location of the ruins of Lussonium, an ancient Roman fort. The mapping of recent movements was based on questionnaire and multiple field surveys. During our studies we also analyzed and mapped the age and building material of the damaged houses. Our results indicate that 19% of the residential buildings have suffered severe damages due to the surface movement over the last decade. The north and west-facing slopes of the Vörösmalom-árok are the most severely damaged areas in Dunakömlőd. We concluded that in addition to the directly erodible edge of the high bluffs, the background areas are also jeopardized by land movements due to improper selection of property development sites.
Keywords: mass movements; lateral erosion; landslide; loess; Danube; Quaternary